The perversion of virtue: understanding murder-suicide - Joiner, Thomas Jr. (Oxford Univ. Press, 2014)
"Of the approximately 38,500 deaths by suicide in the U.S. annually, about two percent - between 750 and 800 - are murder-suicides. The horror of the murder-suicide looms large in the public consciousness-they are reported in the media with more frequency and far more sensationalism than most suicides, and yet very little research has been conducted on this grave form of violence. In The Perversion of Virtue, suicide researcher Thomas Joiner explores the nature of murder-suicide and offers a unique new theory to explain this nearly unexplainable act: that 'true' murder-suicides always involve the wrongheaded invocation of one of four interpersonal virtues: mercy, justice, duty, and glory. The parent who murders his child and then himself seeks to 'save' his child from a fatherless life of hardship; the wife who murders her husband and then herself seeks to right the wrongs he committed against her, and so on. Rather than distorting these four virtues beyond recognition, murder-suicide involves the gross misperception of when and how these virtues should be applied. Drawing on case studies from the media as well as from scholarly literature, Joiner meticulously examines, deconstructs, and finally rebuilds our understanding of murder-suicide in such a way as to bring tragic reason to what may seem an unfathomable act of violence. Along the way he also dispels some of the most enduring myths of suicide - for instance, that suicide is usually an impulsive act (it is almost always premeditated), or that alcohol or drugs are involved in most suicides (usually they are not). Sure to be controversial, this book seeks to make sense of one of the most difficult-to-comprehend types of violence in modern society, shedding new light that will ultimately lead to better understanding and even prevention"--